Biological gel-based microchamber array for tumor cell proliferation and migration studies in well-controlled biochemical gradients. Issue 15 (23rd June 2021) - Yao, Jingru; Li, Guoqiang; Jiao, Yang; Zheng, Yu; Liu, Yanping; Wang, Gao; Zhou, Lianjie; Zhang, Hongfei; Zhang, Xianquan; Shuai, Jianwei; Fan, Qihui; Ye, Fangfu; et al.
Abstract : A microchamber array with composite ECM device enables the construction of a more realistic model for investigating cancer migration mechanisms and has potential to serve as a platform for personalized medicine screening. Abstract : Breast cancer metastasis is a complex process controlled by multiple factors, including various cell–cell interactions, cell–environment coupling, and oxygen, nutrient and drug gradients that are intimately related to the heterogeneous breast tissue structure. In this study, we constructed a high-throughput in vitro biochip system containing an array of 642 microchambers arranged in a checkerboard configuration, with each chamber embedded in a composite extracellular matrix (ECM) composed of engineered collagen and Matrigel to mimic local heterogeneous environment in vivo . In addition, a controllable complex tetragonal chemical concentration profile can be achieved by imposing chemical compounds at the four boundaries of the chip, leading to distinct local nutrient and/or drug gradients in the individual microchambers. Here, the microchamber array with composite ECM (MACECM) device aims to simulate multiple tumor cell niches composed of both breast epithelial cells (MCF-10A-GFP) and metastatic breast cancer cells (MDA-MB-231-RFP), which enables systematic studies of cell responses to a variety of biochemical conditions. The results obtained from the MACECM studies indicate that discoidin domain receptor 1 (DDR1) inhibitor 7rh and matrix metalloproteinase inhibitor batimastat, in association with epidermal growth factor (EGF) had no significant effects on the growth of MCF-10A-GFP cells, but had significant effects on DDR1 expression and the related migratory behavior of MDA-MB-231-RFP cells. The MACECM design not only enables the construction of a more realistic in vitro model for investigating cancer cell migration mechanisms but also has considerable potential for further development as a platform for next-generation high-throughput and therapeutic screening ( e.g., anti-cancer drug evaluation) and personalized medicine.